THE EFFECT OF CORRUPT BEHAVIOR ON THE FLOW OF FOREIGN DIRECT INVESTMENT TO INDONESIA - Posma Sariguna Johnson Kennedy (Asia Pacific Fraud Journal, 2018)
The objective of this paper is to find out whether corrupt behavior can affect the foreign investment flow to Indonesia. Corrupt behavior in Indonesia is proxyed using Corruption Perceptions Index (CPI) issued by Transparency International institution. This study was conducted empirically through a single model built using a gravity model with panel data regression. The variables included in the model are capital flows, bilateral factor, economic size of home country, economic size of host country, barrier of investment, and global factors. The bilateral factor is reviewed using the competition of foreign investment flow to China. The investment constraint, in the form of corruption, is reviewed using the Corruption Perceptions Index (CPI). The result of the research shows that foreign investors are very concerned about corruption in Indonesia which is considered as a barrier and obstacle in investment. The high level of corruption has resulted in a decrease in the flow of foreign direct investment into Indonesia. This should be cautioned because corruption in Indonesia has had a negative effect on the investment climate in Indonesia.